Fifty years of compositional changes in US out-migration, 1908-1957 - Costanza Biavaschi (Institute for the Study of Labor (IZA), 2013)
Immigration authorities have seldom collected data on the out-migration of the foreign-born. As a consequence, several indirect approaches have been proposed to measure and study out-migration. This paper adds to the literature by using official statistics that directly identify the out-migration by demographic and socio-economic characteristics. Using time series and panel methods on the composition of U.S. out-migration between 1908 and 1957, the paper asks two questions. First, how did the out-migrants compare with in-migrants and permanent settlers? Second, did the economic and political events of the 1900s have any impact on the composition of this outflow? Results show that the out-migrants were primarily unskilled workers, but selection has become more positive over time. The economic and political shocks of the first half of the 20th century impacted the composition of the outflow, however, the more restrictive immigration policies have been associated primarily with longer stays. These findings complements the results based on indirect measures of out-migration, and are interestingly in line with analyses of out-migrant selectivity and impact of border controls on out-migrant behavior in later periods.
Keywords: F22; J61; N12; K37; 330; return migration; out-migration; self-selection; quotas